SEVERAL FACTORS ASSOCIATING WITH CONTACT DERMATITIS ON OIL PALM PLANTATIONS WORKERS IN BELUTU VILLAGE, KANDIS SUBDISTRICT IN 2016 - - Muhamadiah (Sistem Informasi, 2017)
Contact dermatitis is skin infection occurring because of allergen and irritant material. Data of Kandis Health Center show 389 cases of dermatitis, 97 cases among cases of dermatitis are oil palm plantation workers living in Belutu Village. The objective of research is to detect factors associating with contact dermatitis on oil palm plantations workers in Belutu Village. The design type of occurrence research is case control study. Population of cases is 97 workers suffering from contact dermatitis and population of control is 1235 workers who are not suffering from contact dermatitis. Based on case control study in which one cases and two control, significant level of 5%, power of test 90%, it is 81 cases and 162 controls taken from each population by systematic random sampling. Analysis of data consists of one variable, two variables, and multiple logistic regressions analysis. Chemical contact (CI 95% OR: 1,34 – 4,12), without Personal Protective Equipment (PPE) (CI 95% OR: 1,110 – 3,405), poor Personal hygiene CI 95% OR: 1,087 – 3,415), associating with contact dermatitis. Chemical contact, without using PPE, and poor personal hygiene effect the occurrence of contact dermatitis on oil palm plantations workers in Belutu Village. Recommendation is to avoid chemical contact, use PPE and improve personal hygiene. Suggestion formulated based on the recommendation.